2014
DOI: 10.1055/s-0034-1367073
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Replacement Strategy during a 27-Km Trail Run in Hot and Humid Conditions

Abstract: The "Abstract" contains an error in following sentence:"Core temperature and the scores of perceived thermal and comfort sensations were signifi cantly higher at the 11 th km and at the end of the race compared to before the race, but not at the 11 th km compared to before the race."The sentence was changed in "Core temperature and the scores of perceived thermal and comfort sensations were signifi cantly higher at the 11 th km and at the end of the race compared to before the race, but not at the 11 th km com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This in addition to the reports from the swimmers of no urine excretion during the events further supports that they drank very little during the Competition. The swimmers' core temperature increased up to a mean 38.3 °C (i. e., a mean 0.9 °C increase or a mean 0.44 °C.h − 1 increase), which is comparable to that noted in swimmers in similar environmental and exercise conditions [15] but lower than in other land-based observations [1,6]. The relatively small increase in core temperature noted in the present official international open water competition, despite the low water intake and the relatively warm water (warmer than the swimming pool temperature usually noted in studies), might be explained by the swimmers' being acclimatized (i. e., have developed hypervolemia) [14] to the tropical climate at the moment of the tests.…”
Section: Competitionsupporting
confidence: 65%
See 1 more Smart Citation
“…This in addition to the reports from the swimmers of no urine excretion during the events further supports that they drank very little during the Competition. The swimmers' core temperature increased up to a mean 38.3 °C (i. e., a mean 0.9 °C increase or a mean 0.44 °C.h − 1 increase), which is comparable to that noted in swimmers in similar environmental and exercise conditions [15] but lower than in other land-based observations [1,6]. The relatively small increase in core temperature noted in the present official international open water competition, despite the low water intake and the relatively warm water (warmer than the swimming pool temperature usually noted in studies), might be explained by the swimmers' being acclimatized (i. e., have developed hypervolemia) [14] to the tropical climate at the moment of the tests.…”
Section: Competitionsupporting
confidence: 65%
“…This very limited water ingestion resulted in a loss of 0.87 kg during the 10-km race (i. e., − 0.44 kg per h), which is lower than that usually noted in other land-based endurance sports of similar duration and environmental conditions [1,6], greater than the loss noted by Maughan et al [20] in a swimming pool, and similar to the loss noted by Hue et al [15] in the present swimmers during experimental swimming pool tests. Most of the body mass decrease in land-based endurance events is due to sweat loss [2], but the swimmers of the present study showed a mean 0.48 L.h − 1 sweat loss rate, which is very low for land-based exercise in a tropical environment: Byrne et al [6] reported 1.47 L.h − 1 and Baillot et al [1] reported 1.2 l.h − 1 . On the other hand, this rate is similar to those noted by Maughan et al [20] in a neutral temperature swimming pool and by others in 29 °C water [8,31].…”
Section: Competitionmentioning
confidence: 66%
“…Hoffman and Stuempfle observed no advantage to sodium-enriched beverages during a 161-km ultramarathon performed by all levels of athletes in heat (38 C) [69]. This result may have been due to a variation in sodium intake from solid food and/or to a better tolerance of faster runners to hypohydration and hyperthermia [14,70].…”
Section: Hydration Policy and Implementationmentioning
confidence: 97%
“…Indeed, most high-level runners exhibit the greatest increase of internal temperature, probably due to higher thermogenesis consecutive to higher workloads. Faster trail runners (27 km) [70] and multi-stages trail runners (127 km on six days) [14] also present a greater post-race dehydration, which could be reduced by cold water due to its effect on voluntarily increasing water absorption during exercise. The higher temperature and greater dehydration observed in faster trail runners also seem to indicate that performance in heat is with the ingestion of neutral water (orange), cold water (blue) and ice-slurry (green).…”
Section: Cooling Policy and Implementationmentioning
confidence: 99%
“…We demonstrated earlier that tropical climate impaired aerobic performance in ecological conditions. We thus found it interesting to evaluate whether hot/humid conditions would be more stressful than hot/dry conditions on physiological functions [9,10], as compared with a control condition.…”
Section: Introductionmentioning
confidence: 99%